Functional, communicative and critical health literacy among older Polish citizens - Anna Mirczak (Nofer Institute of Occupational Medicine, 2022)
Background The level of health literacy possessed by an individual (functional, communicative, critical) determines their ability to effectively self-manage a chronic disease. The aim of the study was to assess the level and functional, communicative, and critical determinants of health literacy in the group of chronically ill older adults. Material and Methods The study was conducted on a representative sample of chronically ill people (N = 400) aged ≥65 years, living in Poland. Three levels of health literacy were measured on the basis of the Functional, Communicative and Critical Health Literacy scale (FCCHL), employed in Polish social research for the first time. Results The conducted research showed that the average health literacy score of the surveyed older adults, measured on the basis of the FCCHL scale, was 2.81±0.71 (M±SD), whereas for the functional subscale of health literacy it was 3.06±0.58 (M±SD), for communicative health literacy it was 2.82±0.86 (M±SD), and for critical health literacy - 2.71±0.92 (M±SD). In terms of functional health literacy, the surveyed seniors most frequently reported problems with reading health-related information, resulting from the use of inadequate font size in information leaflets and brochures. Questions included in the subscale representing communicative health literacy revealed that the majority of the respondents understood the provided information about diseases, nevertheless they were reluctant to share thoughts about their health with other people. Within the framework of critical health literacy, one-third of the respondents did not search for any additional information, trusting that the information obtained was accurate and reliable. Conclusions The surveyed elderly people rated worse their level of communicative and critical health literacy compared to the functional level. As a consequence of the low level of communicative and critical health literacy of the surveyed older adults, a certain deficit in their self-managing a disease entity is forecast. Med Pr. 2022;73(3):191-9